Motor interference of incongruent motions increases workload in close HRI. (18th March 2020) - Kühnlenz, Kolja; Kühnlenz, Barbara
Abstract : This paper investigates the effect of motor interference in human arm motions performed in close vicinity to robot arm motions and resulting workload. Human and robot perform congruent (parallel) and incongruent (orthogonal) motions in front of each other and hand positions are recorded through an optical tracking system. The experimental results show a significant increase of human hand position variability as well as a decrease of perceived performance and an increase of perceived effort between congruent and incongruent motion conditions. Moreover, it is found that an increase of motor interference results in higher workload. The results further suggest that even though humanoid form might be considered more intuitive in close human–robot interaction, humanoid design of an interacting robot might not always be the best choice in terms of cooperative positioning accuracy and workload. GRAPHICAL ABSTRACT: